Tocilizumab In Severe To Critical Confirmed COVID-19: A Case Series At Ulin Referral Hospital Of South Kalimantan - Haryati Haryati; Fidya Rahmadhany Arganita; Widya Ramadhaniati (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new type of coronavirus that causes pneumonia. The clinical severity of COVID-19 is related to the presence of a “cytokine storm” that causes overproduction of inflammatory mediators such as interleukin (IL)-6. Tocilizumab (TCZ) as an IL-6 inhibitor is subject of major studies as a potential therapeutic agent. This study reported 20 cases of COVID-19 patients being treated with the IL-6 inhibitor TCZ beside standard therapy. Patients were followed up on clinical, laboratory and chest x-rays before and after the administration of therapy which were report descriptively. The oxygen saturation of patients who survived shows rapid improvements. The laboratory results showed that CRP decreased after administration TCZ immediately. Meanwhile, other markers improve slowly, such as leucocytes, Neutrophyl Lymphocyte Ratio (NLR), Absolute Lymphocyte Count (ALC) and Lactate Dehydrogenase (LDH) but ferritin was tended to fluctuate. In chest X-ray’s, infiltrate bilateral on admission began to diminished until almost disappeared on the 14th day after TCZ. From 20 patients, 80% of patients survived with improvement in clinical, laboratory and chest X-rays, while the rest death with a good response on first therapy but fluctuated and worsened before death. Tocilizumab can be considered to provide clinical improvements in severe and critical COVID-19 patients.